Perceived Usefulness and Ease of Use Towards the Intention of Using Drone Technology among Micro Farmers in Malaysia - Ahmad, Nurazwa; Zainudin, Izzah Farwizah; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2023)
Drones can perform various functions that lead to improvements in agricultural activities. The scopes of drone operations are irrigation, crop health monitoring, planting, crop spraying, crop inspection and soil analysis. The problems encountered in the use of drone technology that monitors crops and fertilizer sowing in farms in the country has not yet become a common norm and most of the efforts are still at the research stage carried out by government agencies and the initial cost of using the technology is high. This study aims to identify the level of intention to use drone technology in the agricultural industry among farmers, along with the level of perception of usefulness (PU) and ease of use (PEOU) of the drone technology, and the relationship between these two factors towards the intention to use drone technology. This study uses quantitative method focusing on Batu Pahat district with the total 173 micro farmers were involved in the survey questionnaire. The Statistical Package for Social Sciences (SPSS) was used for the data analyses. The results show all variables were recorded a moderate level among the farmers. The correlation coefficient between the perceived usefulness and the intention to use technology is r=0.668 whereas for perceived ease of use and the intention to use technology is r=0.623, both were statistically significant at p